Accurate determination of active slip systems for improved geometrical criteria of basal-to-basal slip transfer at grain boundaries in pure Mg. (15th January 2023) - Sarebanzadeh, Maral; Orozco-Caballero, Alberto; LLorca, Javier
Abstract: Basal-to-basal slip transfer across grain boundaries was analyzed through the combination of slip trace analysis and electron back-scatterer diffraction in weakly-textured pure Mg specimens deformed in tension. Basal slip was the dominant deformation mechanism in many grains, and slip transfer/blocking was assessed at 103 grain boundaries. In addition, the actual active slip system(s) in 170 grains were determined through the analysis of the grain rotation as a result of plastic slip along the basal slip systems. Finally, the twist angle θ (formed between the traces of both active slip planes in the grain boundary plane) was determined in selected cases by the progressive removal of the material by a focus ion beam to measure the grain boundary orientation within the sample. It was found that the basal slip system with the highest global Schmid factor was the most active one in only 49.3% of the grains. In 25.7% of the grains, the basal slip system with the highest Schmid factor was not active. The analysis of basal-to-basal slip transfer/blocking showed that slip transfer is likely to occur if m α β ′ > 0.73. In the cases in which m α β ′ > 0.73 and slip transfer did not occur, it was found that the twist angle θ > 60°. Moreover, slip transfer is unlikely to take place if the trace of one of the active slip systems across the boundary is parallel to the grain boundary. Graphical abstract: Image, graphical abstract